1996
DOI: 10.1046/j.1365-313x.1996.10040655.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of abscisic acid‐deficient Arabidopsis mutants at two new loci

Abstract: Novel Arabidopsis mutants with lowered levels of endogenous abscisic acid (ABA) were isolated. These were selected in a screen for germination in the presence of the gibberellin biosynthesis inhibitor paclobutrazol. Another mutant was isolated in a screen for NaCl tolerance. The ABA-deficiency was caused by two monogenic, recessive mutations, aba2 and aba3, that were both located on chromosome 1. The mutants showed a phenotype that is known to be characteristic for ABA-deficiency: a reduced seed dormancy and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
413
1
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 445 publications
(442 citation statements)
references
References 0 publications
23
413
1
5
Order By: Relevance
“…Possible mechanisms for ABA modulation of sugar signalling are suggested by the observation that the SNF1-related kinase PKABA1 is induced in barley aleurone layers by ABA, and that its constitutive expression drastically suppressed aamylase expression (Go  mez-Cadenas et al, 1999). In Arabidopsis, the requirement for GA during seed germination has been used to isolate ABA-de®cient mutants (Le  on- Kloosterziel et al, 1996) and, consistent with the predictions of our model, abi4 mutants are able to germinate in the presence of the gibberellin biosynthesis inhibitor paclobutrazol (Laby et al, 2000). In the absence of ABA signalling promoting a storage mode, less activation of a mobilization mode by gibberellins may be required.…”
Section: Discussionmentioning
confidence: 99%
“…Possible mechanisms for ABA modulation of sugar signalling are suggested by the observation that the SNF1-related kinase PKABA1 is induced in barley aleurone layers by ABA, and that its constitutive expression drastically suppressed aamylase expression (Go  mez-Cadenas et al, 1999). In Arabidopsis, the requirement for GA during seed germination has been used to isolate ABA-de®cient mutants (Le  on- Kloosterziel et al, 1996) and, consistent with the predictions of our model, abi4 mutants are able to germinate in the presence of the gibberellin biosynthesis inhibitor paclobutrazol (Laby et al, 2000). In the absence of ABA signalling promoting a storage mode, less activation of a mobilization mode by gibberellins may be required.…”
Section: Discussionmentioning
confidence: 99%
“…The following Arabidopsis thaliana T-DNA insertion mutants were used in this study: bam1 (Salk_039895), bam3 (CS92461) (Fulton et al, 2008), amy3-2 (Sail_613 D12) , amy3 bam1 (Horrer et al, 2016), snrk2.2 snrk2.3 snrk2.6 (Fujii and Zhu, 2009), areb1 areb2 abf3 (Yoshida et al, 2010), aao3-4 (Salk_072361) (Seo et al, 2004), nced3 (GABI_129B08) (Wan and Li, 2006), and aba2-1 (G1464A) (Léon-Kloosterziel et al, 1996). Arabidopsis ecotype Columbia-0 (Col-0) was used as the wild type in all experiments.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…The absence of ABA-induced dormancy allows seeds to germinate without gibberellins. Therefore, the selection of mutants that germinate in the presence of GA biosynthesis inhibitors, such as paclobutrazol and tetcyclacis, is an effective way to isolate ABA biosynthesis mutants (Léon- Kloosterziel et al, 1996b). Reciprocal crosses between wild type and the ABA deficient aba1 mutants showed that dormancy is controlled by the ABA genotype of the embryo and not by that of the mother plant.…”
Section: Genes and Factors Affected In Seed Dormancy/germinationmentioning
confidence: 99%